The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/ph14020134
|View full text |Cite
|
Sign up to set email alerts
|

Liquid and Vapor Phase of Four Conifer-Derived Essential Oils: Comparison of Chemical Compositions and Antimicrobial and Antioxidant Properties

Abstract: In this study, the chemical composition of the vapor and liquid phase of Pinus cembra L., Pinus mugo Turra, Picea abies L., and Abies Alba M. needles essential oils (EOs) was investigated by Headspace-Gas Chromatography/Mass Spectrometry (HS-GC/MS). In the examined EOs, a total of twenty-eight components were identified, most of which belong to the monoterpenes family. α-Pinene (16.6–44.0%), β-pinene (7.5–44.7%), limonene (9.5–32.5%), and γ-terpinene (0.3–19.7%) were the most abundant components of the liquid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 67 publications
3
31
0
Order By: Relevance
“…The Petri plates were sealed with parafilm in order to prevent any vapor leakage. After 24 h of incubation, the inhibition halo was measured by a vernier caliper rule [33]. The means and standard deviations were obtained by triplicate measures of the Agar disk-diffusion and VPT halos.…”
Section: Agar Disk-diffusion Methods and Vapor Phase Test (Vpt)mentioning
confidence: 99%
See 1 more Smart Citation
“…The Petri plates were sealed with parafilm in order to prevent any vapor leakage. After 24 h of incubation, the inhibition halo was measured by a vernier caliper rule [33]. The means and standard deviations were obtained by triplicate measures of the Agar disk-diffusion and VPT halos.…”
Section: Agar Disk-diffusion Methods and Vapor Phase Test (Vpt)mentioning
confidence: 99%
“…Their aroma can be more or less intense depending on their content of molecules that provide a potential biological effect, making the hydrolates useful for the food industry as preserving and/or aromatic agents [31]. In this study, for the first time, to better describe the vapor phase chemical profiles of Hys and EOs obtained from flowers and inflorescences of R. officinalis and inflorescences of L. angustifolia growing in Tuscany, we used the automated headspace sampler directly coupled with gas chromatography-mass spectrometry (HS/GC-MS) [32,33]. This sampling technique is conservative and non-destructive and does not require the use of solvent for the extraction process, thus avoiding a possible loss of components.…”
Section: Introductionmentioning
confidence: 99%
“…The antimicrobial activity of fir and pine oils have been frequently reported as well, however, mostly with regard to bacteria and fungi pathogenic to humans. In the experiment of Garzoli et al [22], fir essential oil showed the highest antibacterial activity against Acinetobacter bohemicus and Bacillus cereus among four tested oils. Moreover, the authors observed that the vapor phase of all tested essential oils was more active than liquid phase.…”
Section: Introductionmentioning
confidence: 90%
“…Tanase et al [83] In a comparative study of the essential oils of four Pinus species, Mitic et al [86] observed that the sensitivity of the tested bacterial pathogens is related to the cell wall structure. Different mechanisms of action can explain the antimicrobial activities of cones, and their wide variety of molecular components can act at multiple levels [87]. Generally, Gram-negative bacteria are more resistant than Gram-positive bacteria because the cell wall does not allow entrance into the cell of hydrophobic molecules present in the cone extracts [88,89].…”
Section: Antibacterial Effects Of the Cone Extractsmentioning
confidence: 99%